Political Polarization and Media Influence: A Comprehensive Analysis - Lal, Suruchi (Political Science Journal, 2024)
In this contemporary era of the 21st century, where information is ubiquitous and the media serves as a mirror of society, this research analyzes the compelling interplay between political polarization and media influence. The escalating divide in political ideologies has become a pervasive concern, prompting an exploration into the role media plays in shaping and, potentially, bridging this gap. The purpose of this study is to unravel the intricate mechanisms underlying the relationship between media and political polarization, with a specific focus on the qualitative analysis of media content and its impact on public opinion. The study aims to generalize global cases while closely observing the situation in Nepal. Employing rigorous qualitative methods, including content analysis of news articles, social media posts, and television broadcasts, the research seeks to unveil the subtleties of how media narratives contribute to the polarization landscape. Drawing upon the theoretical foundations of agenda-setting and framing, the study aims to decipher how media not only reflects but also molds political discourse. Preliminary findings suggest a nuanced connection between media exposure, issue framing, and individual political attitudes. The research concludes by shedding light on the complex dynamics of media influence on political polarization, offering valuable insights for refining media practices and fostering a more informed and balanced public discourse. This investigation contributes a deeper understanding of the symbiotic relationship between media and political polarization, paving the way for informed strategies to navigate and mitigate this contemporary societal challenge.